2021
DOI: 10.34172/ajmb.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric Oil: Composition, Extraction, Potential Health Benefits and Other Useful Applications

Abstract: The turmeric essential oil of Curcuma species has extensively more useful properties due to its rich phytochemical profile. The concentration of volatile chemical constituents varies according to their type of applied plant part (i.e., root, rhizome, leaves, and flower) for extraction and type of the adopted extraction method. Novel extraction and purification methods, subcritical CO2 , supercritical CO2 , pressurized liquid extraction, and molecular distillation are found to be more efficient for good recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…Turmerone was found to be the major chemical compound in turmeric EO, comprising 68.46% of its composition ( Table 1 ). This is in line with other reports that have demonstrated turmerone as a major compound in turmeric EO, accounting for around 60% of its composition, possibly in the forms of ar -turmerone, α-turmerone, and β-turmerone ( Jayaprakasha et al, 2005 ; Liju et al, 2011 ; Jaiswal and Naik, 2021 ). However, variations in EO composition can occur due to factors such as geographical location, season, growth stage, and plant parts used.…”
Section: Discussionsupporting
confidence: 93%
“…Turmerone was found to be the major chemical compound in turmeric EO, comprising 68.46% of its composition ( Table 1 ). This is in line with other reports that have demonstrated turmerone as a major compound in turmeric EO, accounting for around 60% of its composition, possibly in the forms of ar -turmerone, α-turmerone, and β-turmerone ( Jayaprakasha et al, 2005 ; Liju et al, 2011 ; Jaiswal and Naik, 2021 ). However, variations in EO composition can occur due to factors such as geographical location, season, growth stage, and plant parts used.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were in agreement with previous studies by Pino et al (2018) , who reported that turmerone (58.9%) was the most represented class of volatiles from rhizomes grown in Amazonian Ecuador, including ar-turmerone (45.5%) and alpha-turmerone (13.4%). Similar results were performed by Jaiswal and Naik (2021) , Guimarães et al . (2020) , Intirach et al (2012) , and Devkota and Rajbhandari (2016) , whose data indicated that 58%, 50.05%, 49.21%, and 25.93% of turmerone were revealed as the major constituents, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The fresh rhizomes of turmeric were cut and chopped into small pieces. Then, turmeric essential oil extraction was carried out by the hydro-distillation method in Clevenger’s apparatus ( Hashimot o et al , 2016 ; Wesołowska et al , 2019 ; Jaiswal and Naik, 2021 ). The extracted essential oils were kept in a light-resistant, tightly sealed container and maintained at 4 ° C before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered an agent with potential anti-tumour, anti-inflammatory, or antiviral effects. [136][137][138] Zedoary oil contains bioactive compounds such as elemene, curcumol, curdione, germacrone, and pinene, which contribute to its pharmacological activities. Studies have shown that Zedoary oil and β-elemene can inhibit cell cycle progression, leading to G2/M and G0/G1 cell cycle arrests.…”
Section: Zedoary Turmeric Oilmentioning
confidence: 99%